Bureaucracy and democracy: the case for more bureaucracy and less democracy - Meier, Kenneth J. (1997)
In "Democracy and Bureaucracy" Meier argues that the bureaucracy problem in the United States is, in reality, a governance problem. Framed in this way, he argues the key problems are failures of electoral institutions rather than failures of bureaucracy. As a result, public administration needs to broaden its focus and include the study of electoral institutions as well as the study of bureaucracy. Effective governance is possible only if students of public administration return to their reformist roots and address both bureaucratic and electoral institutions. As a starting point in such a debate, Meier proposes a series of reforms for U.S. political institutions. - Reproduced
Keywords: Bureaucracy - United States; Bureaucracy